SIFAT-SIFAT RUANG TOPOLOGI T_2Δ - Erik Maurten Firdaus; Ade Ima Afifa Himayati (JURNAL ILMU KOMPUTER DAN MATEMATIKA, 2023)
A topological space  is called if   is a  spaces and for every open set   and   In this paper, we investigate some properties of  space. We study hereditary, topological invariant, and the product of finite  spacesA topological space  is called if   is a  spaces and for every open set   and   In this paper, we investigate some properties of  space. We study hereditary, topological invariant, and the product of finite  spaces